The association between violent video game exposure and sub-types of school bullying in Chinese adolescents - She, Yuhang; Yang, Zidan; Xu, Lingyu; Li, Liping (Frontiers in Psychiatry, 2022)
Background: School bullying has been a worldwide public health issue in adolescents. Adolescents who were exposure to violent video games (VVGs) were more aggressive. However, research on the association between violent video game exposure (VVGE) and different types of school bullying was limit in Chinese adolescents. Objective: The purpose of this study was to explore whether VVGE was linked to school bullying behaviors among Chinese adolescents. And to examine the relationship between different levels of violent game exposure and four sub-types (physical, verbal, relational, and cyber) of school bullying involvement. Method: This was a cross-sectional study of 1992 Chinese students (55.02% boys and 44.98% girls) with the average age of 15.84±1.62 years. Sub-types of school bullying victimization and perpetration, Internet addiction, and violent video game exposure (VVGE) were measured by a self-administrated questionnaire. The association was examined with multiple logistic regression analysis, and adjusted for covariates. Results: Physical, verbal, relational, and cyber school bullying victimization were reported by 18.12%, 60.34%, 11.75%, and 12.05% of the adolescents. And physical, verbal, relational, and cyber school bullying perpetration were reported by 16.62%, 54.62%, 21.49%, and 8.23%. Of the students, 1398 (70.18%) reported to be normal Internet user, 514 (25.80%) were moderate Internet addictive, and 31 (1.56%) of the students were severe Internet addictive. The prevalence of no violent video game exposure (VVGE), low-level VVGE, medium-level VVGE, and high-level of VVGE were 27.70%, 24.10%, 24.20%, and 24.00%, respectively. The risk of physical victimization and physical perpetration were significantly increased with the increasing degree level of violent video game exposure (P for trend < 0.001), with the highest adjusted OR were 2.251 (95% CI 1.501-3.375) and 2.554 (95% CI 1.685-3.870) comparing high-level VVGE to no VVGE. Conclusions: These findings highlight the specific association between different sub-types of school bullying involvement and violent video game exposure. Physical school bullying prevention and intervention programs should be prior to adolescents who are involved in violent video games.